Hot rolled steel plate
The development of a hot rolled steel sheet with a tailored chemical composition and metal structure addresses the limitations of existing steel sheets, achieving high strength, improved formability, and enhanced bending resistance for automotive and industrial applications.
Patent Information
- Application Number
- JP2023555044
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-11
- Filing Date
- 2022-09-14
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2042-09-14
AI Technical Summary
Existing hot rolled steel sheets lack high strength, limited reduction in thickness at break, and poor hole spreadability and shear processability, which are essential for lightweight and safe automotive applications.
A hot rolled steel sheet with a specific chemical composition (C: 0.040-0.250%, Si: 0.05-3.00%, Mn: 1.00-4.00%, etc.) and a metal structure comprising over 92% martensite and tempered martensite, along with controlled Entropy, Inverse Differential, and Cluster Shade values, is developed to enhance strength and formability.
The resulting steel sheet achieves high strength, excellent hole spreadability, and shear processability, while also suppressing cracking during bending, making it suitable for various industrial applications including automotive members.
Smart Images

Figure 0007648953000027 
Figure 0007648953000001 
Figure 0007648953000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot-rolled steel sheet. Specifically, the present invention relates to a hot-rolled steel sheet that is used by being formed into various shapes by press working or the like, and in particular to a hot-rolled steel sheet that has high strength and a critical thickness reduction rate at break, and also has excellent hole expandability and shear workability. This application claims priority based on Japanese Patent Application No. 2021-166960, filed on October 11, 2021, the contents of which are incorporated herein by reference. [Background technology]
[0002] In recent years, from the viewpoint of protecting the global environment, efforts are being made in many fields to reduce carbon dioxide emissions. Automobile manufacturers are also actively developing technologies to reduce the weight of vehicles in order to improve fuel efficiency. However, reducing the weight of vehicles is not an easy task, as emphasis is also placed on improving crashworthiness to ensure the safety of passengers.
[0003] In order to achieve both vehicle body weight reduction and crashworthiness, it has been considered to use high-strength steel plates to thin the walls of components. For this reason, there is a strong demand for steel plates that combine high strength with excellent formability, and several technologies have been proposed to meet these demands. Since there are various processing styles for automotive components, the required formability varies depending on the component to which it is applied, but among them, the limit thickness reduction rate at break and the hole expandability are positioned as important indicators of formability. The limit thickness reduction rate at break is a value calculated from the thickness of the tensile test piece before breakage and the minimum value of the thickness of the tensile test piece after breakage. If the limit thickness reduction rate at breakage is low, it is undesirable because it is prone to early breakage when tensile strain is applied during press forming.
[0004] Automotive components are formed by press molding, and the blanks for press molding are often produced by shearing, which has high productivity. Blanks produced by shearing must have excellent end surface accuracy after shearing.
[0005] For example, if the boundary between the fracture surface and the shear surface at the sheared edge has low linearity, the accuracy of the sheared edge significantly deteriorates.
[0006] For example, Patent Document 1 discloses a hot-rolled steel sheet in which the Mn segregation degree and the P segregation degree at the center of the sheet thickness are controlled, and which serves as a raw material for a cold-rolled steel sheet having excellent surface properties after press working. However, Patent Document 1 does not take into consideration the critical sheet thickness reduction rate at break and the shear workability of the hot-rolled steel sheet. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2020 / 044445 [Non-patent literature]
[0008] [Non-Patent Document 1] J. Webel, J. Gola, D. Britz, F. Mucklich, Materials Characterization 144 (2018) 584-596 [Non-Patent Document 2] DL Naik, HU Sajid, R. Kiran, Metals 2019, 9, 546 [Non-Patent Document 3] K. Zuiderveld, Contrast Limited Adaptive Histogram Equalization, Chapter VIII.5, Graphics Gems IV. PS Heckbert (Eds.), Cambridge, MA, Academic Press, 1994, pp. 474-485 Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a hot-rolled steel sheet having high strength and a critical sheet thickness reduction rate at break as well as excellent hole expandability and shear workability. [Means for solving the problem]
[0010] The gist of the present invention is as follows. (1) A hot-rolled steel sheet according to one aspect of the present invention has a chemical composition, in mass%, C: 0.040~0.250%, Si: 0.05 to 3.00%, Mn: 1.00-4.00%, Sol.Al: 0.001~0.500%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, Ti: 0 to 0.300%, Nb: 0 to 0.100%, V: 0 to 0.500%, Cu: 0-2.00%, Cr: 0-2.00%, Mo: 0-1.00%, Ni: 0-2.00%, B: 0~0.0100%, Ca: 0 to 0.0200%, Mg: 0 to 0.0200%, REM: 0~0.1000%, Bi: 0 to 0.0200%, As: 0~0.100%, Zr: 0-1.00%, Co: 0-1.00%, Zn: 0-1.00%, W: 0 to 1.00%, Sn: 0 to 0.05%, and The balance is Fe and impurities. Satisfying the following formula (A), The metal structure is, in area%, The total content of martensite and tempered martensite is more than 92.0% and not more than 100.0%; The retained austenite is less than 3.0%. Ferrite is less than 5.0%; The entropy value, which is obtained by analyzing the SEM image of the metal structure by a gray level co-occurrence matrix method and is represented by the following formula (1), is 11.0 or more; The inverse differenced normalized value shown by the following formula (2) is less than 1.020, The Cluster Shade value shown in the following formula (3) is -8.0×10 5 ~8.0×10 5 and The standard deviation of the Mn concentration is 0.60 mass% or less; The tensile strength is 980MPa or more. Zr+Co+Zn+W≦1.00% …(A) However, each element symbol in the formula (A) indicates the content of the element in mass %, and 0% is substituted when the element is not contained. Here, P(i,j) in the following formulas (1) to (5) is a gray level co-occurrence matrix, L in the following formula (2) is the number of possible gray scale levels of the SEM image, i and j in the following formulas (2) and (3) are natural numbers from 1 to L, and μ in the following formula (3) is x and μ y are expressed by the following equations (4) and (5), respectively.
number
number
number
number
number
[0011] According to the above-mentioned aspect of the present invention, it is possible to obtain a hot-rolled steel sheet having high strength and a critical thickness reduction rate at break, as well as excellent hole expandability and shear workability. Also, according to the above-mentioned preferred aspect of the present invention, it is possible to obtain a hot-rolled steel sheet having the above-mentioned properties and further suppressing the occurrence of internal cracks in bending, i.e., having excellent resistance to internal cracks in bending. The hot-rolled steel sheet according to the above aspect of the present invention is suitable as an industrial material used for automobile parts, machine structural parts, and further building parts. [Brief description of the drawings]
[0012] [Figure 1] FIG. 13 is a diagram for explaining a method for measuring the linearity of the boundary between the fracture surface and the shear surface at the end face after shearing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The chemical composition and metal structure of the hot-rolled steel sheet according to this embodiment will be described in more detail below. However, the present invention is not limited to the configuration disclosed in this embodiment, and various modifications are possible without departing from the spirit of the present invention.
[0014] In the following, the numerical ranges described with "~" include the lower and upper limits. Numerical values indicated as "less than" or "greater than" are not included in the numerical range. In the following description, % for chemical composition is mass % unless otherwise specified.
[0015] chemical composition The chemical composition of the hot-rolled steel sheet according to this embodiment will be described in detail below.
[0016] C: 0.040~0.250% C increases the area ratio of the hard phase. In addition, C increases the strength of martensite by combining with precipitation strengthening elements such as Ti, Nb, and V. If the C content is less than 0.040%, it is difficult to obtain the desired strength. If the C content is less than 0.040%, the ferrite fraction increases, and the I value also increases due to the influence of the flat ferrite structure. Therefore, the C content is set to 0.040% or more. The C content is preferably 0.060% or more, more preferably 0.070% or more or 0.080% or more. On the other hand, if the C content exceeds 0.250%, the formation of pearlite with low strength is promoted, and the area ratio of martensite and tempered martensite is reduced, resulting in a decrease in the strength of the hot-rolled steel sheet. Also, if the C content exceeds 0.250%, the flat cementite structure increases, and the E value decreases due to the effect of the formation of carbide regions with small brightness differences. Therefore, the C content is set to 0.250% or less or 0.220% or less. The C content is preferably 0.200% or less, 0.170% or less, 0.150% or less, or 0.120% or less.
[0017] Silicon: 0.05 to 3.00% Si has the effect of delaying the precipitation of cementite. This effect can increase the area ratio of martensite and tempered martensite, and can increase the strength of hot-rolled steel sheets through solid solution strengthening. Si also has the effect of improving the soundness of steel through deoxidization (suppressing the occurrence of defects such as blowholes in steel). If the Si content is less than 0.05%, the above effect cannot be obtained. If the Si content is less than 0.05%, the flat cementite structure increases, and the I value also increases due to the effect of the formation of carbide regions with small brightness differences. Therefore, the Si content is set to 0.05% or more. The Si content is preferably 0.50% or more, 0.80% or more, or 1.00% or more. On the other hand, if the Si content exceeds 3.00%, the surface properties, chemical conversion treatability, and weldability of the steel sheet are significantly deteriorated, and the A3 transformation point is significantly increased. This makes it difficult to perform stable hot rolling. Furthermore, if the Si content exceeds 3.00%, the area ratio of ferrite increases, and the E value decreases due to the influence of the flat ferrite structure. Therefore, the Si content is set to 3.00% or less. The Si content is preferably 2.70% or less, more preferably 2.50% or less, 2.20% or less, 2.00% or less, 1.80% or less, or 1.50% or less.
[0018] Mn: 1.00-4.00% Mn has the effect of suppressing ferrite transformation and increasing the strength of hot-rolled steel sheet. If the Mn content is less than 1.00%, the desired strength cannot be obtained. Therefore, the Mn content is set to 1.00% or more. The Mn content is preferably 1.50% or more, 2.00% or more, or 2.30% or more. On the other hand, if the Mn content exceeds 4.00%, the crystal orientation difference of the crystal grains in the hard phase becomes non-uniform due to the segregation of Mn, and the linearity of the boundary between the fracture surface and the shear surface at the end surface after shear processing decreases. In addition, if the Mn content exceeds 4.00%, the area ratio of the retained austenite increases, and the I value also increases due to the influence of the flat retained austenite structure. Therefore, the Mn content is set to 4.00% or less. The Mn content is preferably 3.70% or less, 3.50% or less, 3.20% or less, or 2.90% or less.
[0019] Sol.Al: 0.001~0.500% Like Si, Al has the effect of improving the soundness of steel by deoxidization, and also has the effect of increasing the area ratio of martensite and tempered martensite by suppressing the precipitation of cementite from austenite. If the sol.Al content is less than 0.001%, the above-mentioned effects cannot be obtained. Therefore, the sol.Al content is set to 0.001% or more. The sol.Al content is preferably 0.010% or more, 0.030% or more, or 0.050% or more, and more preferably 0.080% or more, 0.100% or more, or 0.150% or more. On the other hand, if the sol.Al content exceeds 0.500%, the above effects are saturated and it is economically undesirable, so the sol.Al content is set to 0.500% or less. The sol.Al content is preferably 0.400% or less, or more preferably 0.300% or less or 0.250% or less. In the present embodiment, sol. Al means acid-soluble Al, and indicates solute Al that is present in the steel in a solid solution state.
[0020] P:0.100% or less P is an element that is generally contained as an impurity, but it also has the effect of increasing strength by solid solution strengthening. Therefore, P may be actively contained, but P is an element that is easily segregated, and if the P content exceeds 0.100%, the critical fracture thickness reduction rate caused by grain boundary segregation will decrease significantly. Therefore, the P content is set to 0.100% or less. The P content is preferably 0.050% or less, 0.030% or less, 0.020% or less, or 0.015% or less. There is no need to specify a lower limit for the P content, but the lower limit for the P content is 0%. From the viewpoint of refining costs, it may be set to 0.001%, 0.003%, or 0.005%.
[0021] S: 0.0300% or less S is an element contained as an impurity, and forms sulfide-based inclusions in steel to reduce the hole expandability and the critical break thickness reduction rate of hot-rolled steel sheets. If the S content exceeds 0.0300%, the hole expandability and the critical break thickness reduction rate of hot-rolled steel sheets are significantly reduced. Therefore, the S content is set to 0.0300% or less. The S content is preferably 0.0100% or less, 0.0070% or less, or 0.0050% or less. There is no need to specify a lower limit for the S content, but the lower limit for the S content is 0%. From the viewpoint of refining costs, the lower limit for the S content may be set to 0.0001%, 0.0005%, 0.0010%, or 0.0020%.
[0022] N: 0.1000% or less N is an element contained in steel as an impurity, and has the effect of reducing the hole expandability and the critical thickness reduction rate at break of a hot-rolled steel sheet. If the N content exceeds 0.1000%, the hole expandability and the critical thickness reduction rate at break of a hot-rolled steel sheet are significantly reduced. Therefore, the N content is set to 0.1000% or less. The N content is preferably 0.0800% or less, more preferably 0.0700% or less or 0.0500% or less. The lower limit of the N content does not need to be particularly specified, but the lower limit of the N content is 0%. The lower limit of the N content may be 0.0001%. As described later, when one or more of Ti, Nb, and V are contained to refine the metal structure, the N content is preferably 0.0010% or more in order to promote the precipitation of carbonitrides, and more preferably 0.0020% or more, 0.0080% or more, or 0.0150% or more.
[0023] O: 0.0100% or less When O is contained in steel in a large amount, it forms coarse oxides that become the starting point of fracture, causing brittle fracture and hydrogen-induced cracking. Therefore, the O content is set to 0.0100% or less. The O content is preferably set to 0.0080% or less, 0.0050% or less, or 0.0030% or less. The lower limit of the O content is 0%, but in order to disperse a large number of fine oxides during deoxidation of molten steel, the O content may be set to 0.0005% or more, or 0.0010% or more.
[0024] In addition to the above elements, the hot-rolled steel sheet according to this embodiment may contain the following elements as optional elements. When no optional elements are contained, the lower limit of the content is 0%. The optional elements will be described in detail below.
[0025] Ti: 0.001 to 0.300% Nb: 0.001 to 0.100% V: 0.001 to 0.500% Since Ti, Nb, and V all precipitate in steel as carbides or nitrides and have the effect of refining the metal structure by the pinning effect, one or more of these elements may be contained. In order to more reliably obtain the effect of the above action, it is preferable that the Ti content is 0.001% or more, the Nb content is 0.001% or more, or the V content is 0.001% or more. In other words, it is preferable that the content of at least one of Ti, Nb, and V is 0.001% or more. However, even if these elements are contained in excess, the above-mentioned effects become saturated and it is economically undesirable. Therefore, the Ti content is set to 0.300% or less, the Nb content is set to 0.100% or less, and the V content is set to 0.500% or less.
[0026] Cu: 0.01-2.00% Cr: 0.01~2.00% Mo: 0.01 to 1.00% Ni: 0.01 to 2.00% B: 0.0001 to 0.0100% Cu, Cr, Mo, Ni and B all have the effect of increasing the hardenability of hot-rolled steel sheets. Cu and Mo also have the effect of precipitating as carbides in steel at low temperatures to increase strength. Furthermore, when Cu is contained, Ni has the effect of effectively suppressing grain boundary cracking of slabs caused by Cu. Therefore, one or more of these elements may be contained.
[0027] As described above, Cu has the effect of increasing the hardenability of hot-rolled steel sheets and the effect of precipitating as carbides in steel at low temperatures to increase the strength of hot-rolled steel sheets. In order to more reliably obtain the effects of the above-mentioned actions, the Cu content is preferably 0.01% or more, and more preferably 0.05% or more. However, if the Cu content exceeds 2.00%, grain boundary cracking of the slab may occur. Therefore, the Cu content is set to 2.00% or less. The Cu content is preferably 1.50% or less, more preferably 1.00% or less, 0.70% or less, or 0.50% or less.
[0028] As described above, Cr has the effect of increasing the hardenability of hot-rolled steel sheets and the effect of precipitating as carbides in steel at low temperatures to increase strength. In order to more reliably obtain the effects of the above-mentioned actions, the Cr content is preferably 0.01% or more, and more preferably 0.05% or more. However, if the Cr content exceeds 2.00%, the chemical conversion treatability of the hot-rolled steel sheet is significantly reduced. Therefore, the Cr content is set to 2.00% or less. The Cr content is preferably 1.50% or less, more preferably 1.00% or less, 0.70% or less, or 0.50% or less.
[0029] As described above, Mo has the effect of increasing the hardenability of hot-rolled steel sheets and the effect of precipitating in steel as carbides to increase the strength of hot-rolled steel sheets. In order to obtain the above-mentioned effects more reliably, the Mo content is preferably 0.01% or more, and more preferably 0.02% or more. However, even if the Mo content exceeds 1.00%, the above-mentioned effects are saturated and it is not economically preferable. Therefore, the Mo content is set to 1.00% or less. The Mo content is preferably 0.50% or less, more preferably 0.20% or less or 0.10% or less.
[0030] As described above, Ni has the effect of increasing the hardenability of hot-rolled steel sheet. In addition, when Cu is contained, Ni has the effect of effectively suppressing grain boundary cracking of slabs caused by Cu. In order to obtain the above-mentioned effect more reliably, the Ni content is preferably 0.01% or more. Since Ni is an expensive element, it is economically undesirable to contain a large amount of it. Therefore, the Ni content is set to 2.00% or less. The Ni content is preferably 1.50% or less, more preferably 1.00% or less, 0.70% or less, or 0.50% or less.
[0031] As described above, B has the effect of enhancing the hardenability of hot-rolled steel sheet. In order to obtain the effect of this action more reliably, the B content is preferably 0.0001% or more, and more preferably 0.0002% or more. However, if the B content exceeds 0.0100%, the hole expandability of the hot-rolled steel sheet is significantly reduced, so the B content is set to 0.0100% or less. The B content is preferably 0.0050% or less or 0.0025% or less.
[0032] Ca: 0.0001 to 0.0200% Mg: 0.0001 to 0.0200% REM: 0.0001 to 0.1000% Bi: 0.0001 to 0.0200% As: 0.001 to 0.100% Ca, Mg and REM all have the effect of adjusting the shape of inclusions to a preferred shape, thereby improving the hole expandability of hot-rolled steel sheets. Bi also has the effect of refining the solidification structure, thereby improving the formability of hot-rolled steel sheets. Therefore, one or more of these elements may be contained. In order to more reliably obtain the effects of the above-mentioned actions, it is preferable that the content of one or more of Ca, Mg, REM and Bi is 0.0001% or more. However, if the Ca content or Mg content exceeds 0.0200%, or if the REM content exceeds 0.1000%, inclusions are excessively generated in the steel, which may actually reduce the hole expandability of the hot-rolled steel sheets. Also, even if the Bi content exceeds 0.0200%, the effects of the above-mentioned actions are saturated, which is economically undesirable. Therefore, the Ca content and Mg content are set to 0.0200% or less, the REM content is set to 0.1000% or less, and the Bi content is set to 0.0200% or less. The Ca content, Mg content, and Bi content are preferably 0.0100% or less, more preferably 0.0070% or less or 0.0040% or less. The REM content is preferably 0.0070% or less or 0.0040% or less. As reduces the austenite single-phase temperature, thereby refining prior austenite grains and contributing to improving the ductility of the hot-rolled steel sheet. In order to reliably obtain this effect, it is preferable that the As content is 0.001% or more. On the other hand, even if a large amount of As is contained, the above effect is saturated, so the As content is set to 0.100% or less. Here, REM refers to a total of 17 elements consisting of Sc, Y and lanthanides, and the content of the above REM refers to the total content of these elements. In the case of lanthanides, they are added industrially in the form of misch metals.
[0033] Zr:0.01~1.00%, Co:0.01~1.00%, Zn:0.01~1.00%, W:0.01~1.00% Zr+Co+Zn+W≦1.00% …(A) However, each element symbol in the formula (A) indicates the content of the element in mass %, and 0% is substituted when the element is not contained. Sn: 0 to 0.05% Concerning Zr, Co, Zn and W, the inventors have confirmed that the effect of the hot-rolled steel sheet according to the present embodiment is not impaired even if these elements are contained in a total of 1.00% or less. Therefore, one or more of Zr, Co, Zn and W may be contained in a total of 1.00% or less. That is, the value of the left side of the formula (A) may be 1.00% or less, 0.50% or less, 0.10% or less, or 0.05% or less. The contents of Zr, Co, Zn, W and Sn may be 0.50% or less, 0.10% or less, or 0.05% or less, respectively. Since Zr, Co, Zn and W do not need to be contained, the contents of each may be 0%. In order to improve the strength of the steel sheet by solid solution strengthening, the contents of Zr, Co, Zn and W may be 0.01% or more, respectively. The inventors have also confirmed that the effect of the hot-rolled steel sheet according to this embodiment is not impaired even if a small amount of Sn is contained. However, if a large amount of Sn is contained, defects may occur during hot rolling, so the Sn content is set to 0.05% or less. Since Sn does not need to be contained, the Sn content may be 0%. In order to improve the corrosion resistance of the hot-rolled steel sheet, the Sn content may be 0.01% or more.
[0034] The balance of the chemical composition of the hot-rolled steel sheet according to the present embodiment may be composed of Fe and impurities. In the present embodiment, the term "impurities" refers to substances that are mixed in from raw materials such as ore, scrap, or the manufacturing environment, and are permissible within a range that does not adversely affect the hot-rolled steel sheet according to the present embodiment.
[0035] The chemical composition of the above-mentioned hot-rolled steel sheet may be measured by a general analytical method. For example, it may be measured by using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). Sol. Al may be measured by ICP-AES using the filtrate after thermally decomposing the sample with acid. C and S may be measured by the combustion-infrared absorption method, N by the inert gas fusion-thermal conductivity method, and O by the inert gas fusion-non-dispersive infrared absorption method. When the hot-rolled steel sheet has a plating layer on the surface, the plating layer may be removed by mechanical grinding or the like, as necessary, before analyzing the chemical composition.
[0036] Metal structure of hot rolled steel sheet Next, the metal structure of the hot-rolled steel sheet according to this embodiment will be described. The hot-rolled steel sheet according to the present embodiment has a metallographic structure in which, in terms of area %, the total of martensite and tempered martensite is more than 92.0% and 100.0% or less, the retained austenite is less than 3.0%, and the ferrite is less than 5.0%. The entropy value shown in the following formula (1) obtained by analyzing an SEM image of the metallographic structure by a gray level co-occurrence matrix method is 11.0 or more, the inverse differenced normalized value shown in the following formula (2) is less than 1.020, and the cluster shade value shown in the following formula (3) is −8.0×10 5 ~8.0×10 5 and the standard deviation of the Mn concentration is 0.60 mass % or less.
[0037] Therefore, the hot-rolled steel sheet according to this embodiment has high strength and a critical thickness reduction rate at break, while having excellent hole expandability and shear workability. In this embodiment, the metal structure at a 1 / 4 depth position of the sheet thickness from the surface (a region from 1 / 8 depth of the sheet thickness from the surface to 3 / 8 depth of the sheet thickness from the surface) and at a central position in the sheet width direction in a cross section parallel to the rolling direction is specified. The reason is that the metal structure at this position shows a typical metal structure of the steel sheet. The surface referred to here means the interface between the plating layer and the steel sheet when the hot-rolled steel sheet has a plating layer.
[0038] Area ratio of retained austenite: less than 3.0% The retained austenite is a metal structure that exists as a face-centered cubic lattice even at room temperature. The retained austenite has the effect of increasing the hole expandability of hot-rolled steel sheets by transformation-induced plasticity (TRIP). On the other hand, the retained austenite is transformed into high-carbon martensite during shearing, which inhibits stable crack generation and causes a decrease in the linearity of the boundary between the fracture surface and the shear surface at the end surface after shearing. When the area ratio of the retained austenite is 3.0% or more, the above effect becomes apparent and the linearity of the boundary between the fracture surface and the shear surface at the end surface after shearing decreases. Therefore, the area ratio of the retained austenite is less than 3.0%. The area ratio of the retained austenite is preferably 1.5% or less, and more preferably less than 1.0%. Since the smaller the amount of retained austenite, the area ratio of the retained austenite may be 0%. However, it is not easy to make the area ratio of the retained austenite 0%, and the lower limit may be 0.5% or 1.0%.
[0039] Ferrite area ratio: less than 5.0% Ferrite is generally a soft metal structure. If the ferrite contains more than a certain amount, the desired strength may not be obtained, and the area of the sheared surface at the end face after shearing may increase. If the area of the sheared surface at the end face after shearing increases, the linearity of the boundary between the fracture surface and the sheared surface at the end face after shearing decreases, which is not preferable. If the area ratio of ferrite is 5.0% or more, the above-mentioned effect becomes apparent. Therefore, the area ratio of ferrite is less than 5.0%. The area ratio of ferrite is preferably 3.0% or less, more preferably 2.0% or less, and even more preferably less than 1.0%. Since the less ferrite, the more preferable it is, the area ratio of ferrite may be 0%. However, it is not easy to make the area ratio of ferrite 0%, and the lower limit may be 0.5%, 1.0%, or 1.5%.
[0040] Known methods for measuring the area ratio of retained austenite include X-ray diffraction, EBSP (Electron Back Scattering Diffraction Pattern) analysis, magnetic measurement, etc. In this embodiment, the area ratio of retained austenite is measured by X-ray diffraction, which is less susceptible to the effects of polishing (if the effects of polishing are present, the retained austenite may change to other phases such as martensite, making it impossible to measure the true area ratio), and can provide accurate measurement results relatively easily.
[0041] In the measurement of the area ratio of retained austenite by X-ray diffraction in this embodiment, first, in a thickness cross section parallel to the rolling direction at a 1 / 4 depth position (a region from the surface to 1 / 8 depth of the thickness of the plate) and at the center position in the width direction of the plate of the hot rolled steel plate, the integrated intensity of a total of six peaks, α(110), α(200), α(211), γ(111), γ(200), and γ(220), is obtained using Co-Kα radiation, and the volume ratio of retained austenite is calculated using the intensity averaging method. The volume ratio of retained austenite obtained is regarded as the area ratio of retained austenite.
[0042] The area ratio of ferrite is measured by the following method. The plate thickness cross section parallel to the rolling direction is finished to a mirror finish and polished at room temperature for 8 minutes using colloidal silica that does not contain an alkaline solution to remove strain introduced into the surface layer of the sample. At any position in the longitudinal direction of the sample cross section, a region 50 μm long and extending from 1 / 8 of the plate thickness depth from the surface to 3 / 8 of the plate thickness depth from the surface is measured using electron backscatter diffraction at measurement intervals of 0.1 μm to obtain crystal orientation information. For the measurements, an EBSD analysis device consisting of a thermal field emission scanning electron microscope (JEOL JSM-7001F) and an EBSD detector (TSL DVC5 detector) is used. The degree of vacuum inside the EBSD analysis device was 9.6×10 -5 The conditions are: 1. the luminance is 1.0 Pa or less, 2. the acceleration voltage is 15 kV, 3. the probe current level is 13, and 4. the electron beam irradiation level is 62. The observation area is 40,000 μm2 Let us assume that.
[0043] Next, a backscattered electron image is taken in the same field of view. The crystal grains in which ferrite and cementite are precipitated in layers are identified from the backscattered electron image, and the area ratio of the crystal grains is calculated, thereby obtaining the area ratio of pearlite.
[0044] Then, for the crystal grains determined to have a body-centered cubic structure among the crystal grains excluding those determined to be pearlite, the obtained crystal orientation information is used to determine the areas with a Grain Average Misorientation value of 1.0° or less as ferrite using the "Grain Average Misorientation" function installed in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device. At this time, the Grain Tolerance Angle is set to 15°, and the area ratio of the areas determined to be ferrite is obtained, thereby obtaining the area ratio of ferrite.
[0045] Next, out of the areas excluding those determined to be pearlite or ferrite, if the maximum value of the "Grain Average IQ" in the ferrite area is Iα, then the area that exceeds Iα / 2 is extracted (determined) as bainite. The area ratio of bainite is obtained by calculating the area ratio of the areas extracted (determined) as bainite.
[0046] Total area ratio of martensite and tempered martensite: More than 92.0% and less than 100.0% If the total area ratio of martensite and tempered martensite is 92.0% or less, the desired strength cannot be obtained. Therefore, the total area ratio of martensite and tempered martensite is set to more than 92.0%. It is preferably 93.0% or more, 95.0% or more, 97.0% or more, or 99.0% or more. The higher the total area ratio of martensite and tempered martensite, the better, so it may be 100.0%.
[0047] The method for measuring the area fractions of martensite and tempered martensite will be described below. First, to observe the same area as the EBSD measurement area where the ferrite area ratio was measured with an SEM, a Vickers indentation is made near the observation position. After that, the surface contamination is polished away, leaving the structure of the observation surface, and the surface is etched with nital. Next, the same field of view as the EBSD observation surface is observed with an SEM at a magnification of 3000x.
[0048] In the EBSD measurement, among the regions determined to have a structure other than ferrite, the regions that have a substructure within the grains and where cementite precipitates with multiple variants are determined to be tempered martensite. Regions that have a high brightness and where the substructure is not revealed by etching are determined to be "martensite and retained austenite". The area ratios of tempered martensite and "martensite and retained austenite" are obtained by calculating the area ratios of each. The area ratio of martensite is obtained by subtracting the area ratio of retained austenite obtained by the above-mentioned X-ray diffraction from the area ratio of "martensite and retained austenite" obtained. The total area ratio of martensite and tempered martensite is obtained by calculating the sum of the area ratios of martensite and tempered martensite.
[0049] Contamination on the surface of the observation surface can be removed by buffing using alumina particles with a particle size of 0.1 μm or less, or by Ar ion sputtering or other methods.
[0050] The hot-rolled steel sheet according to the present embodiment may contain one or both of bainite and pearlite with a total area ratio of 0% or more and less than 8.0% as a remaining structure. The upper limit of the area ratio of the remaining structure may be 6.0%, 5.0%, 4.0%, 3.0%, or 2.5%.
[0051] In this embodiment, the area ratio of each structure is measured by X-ray diffraction, EBSD analysis, and SEM observation, so the total of the area ratios of each structure obtained by measurement may not be 100.0%. If the total of the area ratios of each structure obtained by the above-mentioned method is not 100.0%, the area ratios of each structure are converted so that the total of the area ratios of each structure becomes 100.0%. For example, if the total of the area ratios of each structure is 103.0%, the area ratio of each structure is multiplied by "100.0 / 103.0" to obtain the area ratio of each structure.
[0052] Entropy value: 11.0 or more, Inverse difference normalized value: less than 1.020 In order to improve the linearity of the boundary between the fracture surface and the shear surface at the end face after shearing, it is important to reduce the periodicity of the metal structure and the uniformity of the metal structure. In this embodiment, the linearity of the boundary between the fracture surface and the shear surface at the end face after shearing is improved by controlling the entropy value (E value) indicating the periodicity of the metal structure and the inverse differenced normalized value (I value) indicating the uniformity of the metal structure.
[0053] The E value represents the periodicity of the metal structure. When the luminance is periodically arranged due to the effect of the formation of a band-shaped structure, that is, when the periodicity of the metal structure is high, the E value decreases. In this embodiment, since it is necessary to have a metal structure with low periodicity, it is necessary to increase the E value. If the E value is less than 11.0, the linearity of the boundary between the fracture surface and the shear surface at the end surface after shear processing is likely to decrease. In a metal structure with high periodicity, that is, a low E value, a crack is generated starting from the periodically arranged structure and running through multiple band-shaped structures present near the starting point to form a fracture surface. As a result, it is estimated that the linearity of the boundary between the fracture surface and the shear surface at the end surface after shear processing is likely to decrease. Therefore, the E value is set to 11.0 or more. It is preferably 11.1 or more, and more preferably 11.2 or more. The higher the E value, the better. There is no particular upper limit to the E value, but it may be 13.5 or less, 13.0 or less, 12.5 or less, or 12.0 or less.
[0054] The I value represents the uniformity of the metal structure, and increases as the area of the region having a certain brightness becomes larger. A high I value means that the uniformity of the metal structure is high. In the hot-rolled steel sheet having a metal structure in which the total area ratio of martensite and tempered martensite is 92.0% or less, which is the present embodiment, it is necessary to make the metal structure mainly composed of martensite with low brightness uniformity. For this reason, in the present embodiment, it is necessary to reduce the I value. When the uniformity of the metal structure is high, that is, when the I value is high, cracks are likely to occur from the tip of the shear tool due to the influence of precipitates and element concentration differences in the crystal grains, and the hardness difference caused by the soft ferrite phase. As a result, the linearity of the boundary between the fracture surface and the shear surface at the end surface after shear processing is likely to decrease. In other words, it is estimated that if the I value is 1.020 or more, the linearity of the boundary between the fracture surface and the shear surface at the end surface after shear processing cannot be improved. Therefore, the I value is less than 1.020. It is preferably 1.015 or less, and more preferably 1.010 or less. The lower limit of the I value is not particularly specified, but it may be 0.900 or more, 0.950 or more, or 1.000 or more.
[0055] Cluster Shade value: -8.0×10 5 ~8.0×10 5 The Cluster Shade (CS) value indicates the degree of distortion of the metal structure. The CS value is positive when there are many points with brightness above the average brightness in the image obtained by photographing the metal structure, and negative when there are many points with brightness below the average brightness.
[0056] In the secondary electron image of a scanning electron microscope, the brightness is high where the surface unevenness of the observed object is large, and the brightness is low where the unevenness is small. The unevenness of the surface of the observed object is greatly affected by the grain size and strength distribution in the metal structure. In this embodiment, the CS value is high when the strength variation of the metal structure is large or the structure unit is small, and is low when the strength variation is small or the structure unit is large.
[0057] In this embodiment, it is important to keep the CS value in a desired range close to 0. 5 If the CS value is less than -8.0×10, the critical thickness reduction rate of the hot-rolled steel sheet decreases. This is presumably because large grains exist in the metal structure and these grains are preferentially fractured during extreme deformation. Therefore, the CS value is -8.0×10 5 More than or equal to -7.5×10 5 More preferably, it is −7.0×10 5 That's all. On the other hand, the CS value is 8.0 × 10 5 When the CS value is more than 8.0×10, the critical thickness reduction rate of the hot-rolled steel sheet at fracture decreases. This is presumably because the microscopic strength variation in the metal structure is large, and the strain during the ultimate deformation is concentrated locally, making the steel sheet more likely to fracture. Therefore, the CS value is 8.0×10 5 The value should be less than 7.5×10 5 More preferably, it is 7.0×10 or less. 5 The following is the result.
[0058] The E value, I value and CS value can be obtained by the following method. In this embodiment, the photographed region of the SEM image (secondary electron image of a scanning electron microscope) taken to calculate the E value, I value, and CS value is a position at a 1 / 4 depth of the plate thickness from the surface (a region from 1 / 8 depth of the plate thickness from the surface to 3 / 8 depth of the plate thickness from the surface) in the plate thickness cross section parallel to the rolling direction, and at the center position in the plate width direction. A Hitachi High-Technologies Corporation SU-6600 Schottky electron gun is used to take the SEM image, with a tungsten emitter and an acceleration voltage of 1.5 kV. With the above settings, the SEM image is output at a magnification of 1000 times and a gray scale of 256 gradations.
[0059] Next, the obtained SEM image is cut into an 880 x 880 pixel region (observation region is 160 μm x 160 μm in actual size) and the image is subjected to smoothing processing with a tile grid size of 8 x 8 and a contrast enhancement limiting factor of 2.0 as described in Non-Patent Document 3. The smoothed SEM image is rotated counterclockwise in 1 degree increments from 0 to 179 degrees, excluding 90 degrees, and an image is created for each degree, resulting in a total of 179 images. Next, for each of these 179 images, the GLCM method described in Non-Patent Document 1 is used to collect the frequency values of brightness between adjacent pixels in the form of a matrix.
[0060] The matrix of 179 frequency values collected by the above method is expressed as p k (k=0 89, 91, 179). For each image, the generated p k is summed for all k (k=0...89, 91...179), and then a 256 × 256 matrix P is calculated in which the sum of each component is normalized to 1. Furthermore, the E value, I value, and CS value are calculated using the following formulas (1) to (5) described in Non-Patent Document 2. In the following formulas (1) to (5), P(i,j) is a gray level co-occurrence matrix, and the value in the i-th row and j-th column of the matrix P is expressed as P(i,j). As described above, the calculation is performed using a 256 x 256 matrix P, so if you want to emphasize this point, you can modify the following formulas (1) to (5) to the following formulas (1') to (5'). Here, L in the following formula (2) is the number of quantization levels of grayscale that the SEM image can take, and in this embodiment, since the SEM image is output in a grayscale of 256 gradations as described above, L is 256. In the following formulas (2) and (3), i and j are natural numbers from 1 to L, and μ in the following formula (3) is x and μ y are expressed by the following equations (4) and (5), respectively. In the following formulas (1') to (5'), the value in the i-th row and j-th column of the matrix P is P ij It is written as follows.
[0061]
number
[0062]
number
[0063]
number
[0064]
number
[0065]
number
[0066]
number
[0067]
number
[0068]
number
[0069]
number
[0070]
number
[0071] Standard deviation of Mn concentration: 0.60 mass% or less The standard deviation of the Mn concentration at the 1 / 4 depth position of the sheet thickness from the surface of the hot rolled steel sheet according to this embodiment (the region from 1 / 8 depth of the sheet thickness from the surface to 3 / 8 depth of the sheet thickness from the surface) and at the center position in the sheet width direction is 0.60 mass% or less. This allows the hard phase to be uniformly dispersed, and prevents the linearity of the boundary between the fracture surface and the shear surface at the end surface after shear processing from decreasing. The standard deviation of the Mn concentration is preferably 0.55 mass% or less or 0.50 mass% or less, and more preferably 0.47 mass% or less. From the viewpoint of suppressing excessive burrs, the lower limit of the standard deviation of the Mn concentration is preferably as small as possible, but due to the constraints of the manufacturing process, the substantial lower limit is 0.10 mass%. If necessary, the lower limit may be 0.20 mass% or 0.28 mass%.
[0072] After mirror polishing the cross section of the hot-rolled steel sheet parallel to the rolling direction, the standard deviation of the Mn concentration is measured at a 1 / 4 depth position of the sheet thickness from the surface (a region from 1 / 8 depth of the sheet thickness from the surface to 3 / 8 depth of the sheet thickness from the surface) and at the center position in the sheet width direction with an electron probe microanalyzer (EPMA). The measurement conditions are an acceleration voltage of 15 kV and a magnification of 5000 times, and a distribution image is measured in a range of 20 μm in the rolling direction of the sample and 20 μm in the thickness direction of the sample. More specifically, the measurement interval is 0.1 μm, and the Mn concentration is measured at 40,000 or more points. Next, the standard deviation is calculated based on the Mn concentrations obtained from all the measurement points to obtain the standard deviation of the Mn concentration.
[0073] Average crystal grain size of surface layer: less than 3.0 μm By making the crystal grain size of the surface fine, it is possible to suppress cracks on the inside of the bend of hot-rolled steel sheets. The higher the strength of hot-rolled steel sheets, the more likely they are to crack from the inside of the bend during bending (hereinafter referred to as cracks on the inside of the bend). The mechanism of cracks on the inside of the bend is presumed to be as follows. During bending, compressive stress is generated on the inside of the bend. At first, the entire inside of the bend is uniformly deformed as the processing progresses, but as the amount of processing increases, the uniform deformation alone is no longer able to support the deformation, and strain is concentrated locally, causing the deformation to progress (generation of shear deformation bands). As this shear deformation band continues to grow, cracks are generated along the shear bands from the inside surface of the bend and grow. It is presumed that the reason why cracks on the inside of the bend are more likely to occur with increasing strength is that the decrease in work hardening ability associated with increasing strength makes it difficult for uniform deformation to proceed, making it easier for deformation bias to occur, which causes shear deformation bands to occur early in processing (or under loose processing conditions).
[0074] The inventors' research has revealed that internal cracks during bending are prominent in steel sheets with a tensile strength of 980 MPa or more. The inventors have also found that the finer the crystal grain size in the surface layer of the hot-rolled steel sheet, the more localized strain concentration is suppressed, and the less likely internal cracks are to occur during bending. In order to achieve the above effect, the average crystal grain size in the surface layer of the hot-rolled steel sheet is preferably less than 3.0 μm. More preferably, it is 2.7 μm or less or 2.5 μm or less. The lower limit of the average crystal grain size in the surface region is not particularly specified, but may be 0.5 μm or 1.0 μm. In this embodiment, the surface layer refers to a region from the surface of the hot-rolled steel sheet to a depth of 50 μm from the surface. As described above, the surface here refers to the interface between the plating layer and the steel sheet when the hot-rolled steel sheet has a plating layer.
[0075] The crystal grain size of the surface layer is measured using EBSP-OIM (Electron Back Scatter Diffraction Pattern-Orientation Image Microscopy) method. EBSP-OIM method is performed using a device that combines a scanning electron microscope and an EBSP analysis device and OIM Analysis (registered trademark) manufactured by AMETEK. The analyzable area of EBSP-OIM method is the area that can be observed by SEM. Although it depends on the resolution of SEM, EBSP-OIM method can analyze with a minimum resolution of 20 nm.
[0076] In a cross section of the hot-rolled steel sheet parallel to the rolling direction, an analysis is performed in at least five fields of view in a region of 40 μm × 30 μm at a magnification of 1200 times in a region from the surface of the hot-rolled steel sheet to a depth of 50 μm from the surface and at the center position in the sheet width direction. A location where the angle difference between adjacent measurement points is 5° or more is defined as a grain boundary, and the area-average grain size is calculated. The obtained area-average grain size is regarded as the average grain size of the surface layer.
[0077] Note that retained austenite is not a structure formed by phase transformation at 600°C or below, and does not have the effect of dislocation accumulation, so it is not included in the analysis in this measurement method (a method for measuring the average crystal grain size of the surface layer). When the area ratio of retained austenite is 0%, it does not need to be excluded from the analysis, but in cases where there is a possibility that it may affect the measurement of the average crystal grain size of the surface layer, the EBSP-OIM method measures retained austenite, which has an fcc crystal structure, by excluding it from the analysis.
[0078] Tensile properties The hot-rolled steel sheet according to this embodiment has a tensile strength (TS) of 980 MPa or more. If the tensile strength is less than 980 MPa, the applicable parts are limited, and the contribution to reducing the weight of the vehicle body is small. The upper limit does not need to be particularly set, but may be 1780 MPa from the viewpoint of suppressing die wear. The tensile strength is measured in accordance with JIS Z 2241: 2011 using a No. 5 test piece of JIS Z 2241: 2011. The tensile test piece is taken from a quarter part from the end in the plate width direction, and the direction perpendicular to the rolling direction is the longitudinal direction.
[0079] Hole expansion characteristics The hot-rolled steel sheet according to this embodiment preferably has a hole expansion ratio (λ) of 55% or more. If the hole expansion ratio (λ) is 55% or more, the applicable parts are not limited, and a hot-rolled steel sheet that contributes greatly to reducing the weight of the vehicle body can be obtained. There is no need to particularly limit the upper limit. There is no need to set an upper limit for the hole expansion ratio λ, but it may be 85% or 80%. The hole expansion ratio (λ) is measured in accordance with JIS Z 2256: 2010 using a No. 5 test piece of JIS Z 2241: 2011. The hole expansion test piece may be taken from a 1 / 4 portion from the end in the plate width direction of the hot rolled steel plate.
[0080] Plate Thickness The thickness of the hot rolled steel sheet according to the present embodiment is not particularly limited, but may be 0.5 to 8.0 mm. By making the thickness of the hot rolled steel sheet 0.5 mm or more, it is easy to ensure the rolling completion temperature and the rolling load can be reduced, and hot rolling can be easily performed. Therefore, the thickness of the hot rolled steel sheet according to the present embodiment may be 0.5 mm or more. It is preferably 1.2 mm or more, 1.4 mm or more, or 1.8 mm or more. Moreover, by making the thickness 8.0 mm or less, it is easy to make the metal structure fine, and the above-mentioned metal structure can be easily ensured. Therefore, the thickness may be 8.0 mm or less. It is preferably 6.0 mm or less, 5.0 mm or less, or 4.0 mm or less.
[0081] Plating layer The hot-rolled steel sheet according to the present embodiment having the above-mentioned chemical composition and metal structure may be provided with a plating layer on the surface for the purpose of improving corrosion resistance, etc., to form a surface-treated steel sheet. The plating layer may be an electroplating layer or a hot-dip plating layer. Examples of the electroplating layer include electrogalvanizing and electrolytic Zn-Ni alloy plating. Examples of the hot-dip plating layer include hot-dip galvanizing, alloyed hot-dip galvanizing, hot-dip aluminum plating, hot-dip Zn-Al alloy plating, hot-dip Zn-Al-Mg alloy plating, and hot-dip Zn-Al-Mg-Si alloy plating. The coating weight is not particularly limited and may be the same as that of the conventional method. In addition, it is also possible to further improve the corrosion resistance by performing an appropriate chemical conversion treatment (for example, application of a silicate-based chromium-free chemical conversion treatment liquid and drying) after plating.
[0082] Manufacturing conditions A suitable method for producing the hot-rolled steel sheet according to this embodiment having the above-mentioned chemical composition and metal structure is as follows.
[0083] In a preferred method for producing a hot-rolled steel sheet according to this embodiment, the following steps (1) to (9) are sequentially performed. Note that the temperature of the slab and the temperature of the steel sheet in this embodiment refer to the surface temperature of the slab and the surface temperature of the steel sheet. Also, the stress refers to the tension applied in the rolling direction of the steel sheet.
[0084] (1) The slab is held in the temperature range of 700 to 850°C for 900 seconds or more, and then further heated and held in the temperature range of 1100°C or higher for 6000 seconds or more. (2) Hot rolling is performed in the temperature range of 850 to 1100°C to reduce the plate thickness by a total of 90% or more. (3) After the rolling stage before the final stage of hot rolling and before the final stage of rolling, a stress of 170 kPa or more is applied to the steel plate. (4) The reduction rate in the final stage of hot rolling is 8% or more, and the hot rolling is completed so that the rolling completion temperature Tf is 900°C or more and less than 960°C. (5) The stress applied to the steel plate after the final stage of hot rolling and before the steel plate is cooled to 800°C is less than 200 kPa. (6) Cool to a temperature range of the hot rolling completion temperature Tf-50°C or less within 1 second after the completion of hot rolling, and then accelerate cool to 600°C at an average cooling rate of 50°C / s or more. However, cooling to a temperature range of the hot rolling completion temperature Tf-50°C or less within 1 second after the completion of hot rolling is a more preferable cooling condition. (7) Cool so that the average cooling rate in the temperature range of 450 to 600°C is 30°C / s or more and less than 50°C / s. (8) Cooling is performed so that the average cooling rate in the temperature range from the coiling temperature to 450°C is 50°C / s or more. (9) Coiling is performed at a temperature of 350°C or less.
[0085] By adopting the above manufacturing method, it is possible to stably manufacture a hot-rolled steel sheet having high strength and a critical thickness reduction rate at break, as well as excellent hole expandability and shear workability. That is, by appropriately controlling the slab heating conditions and the hot rolling conditions, Mn segregation is reduced and the pre-transformation austenite is made equiaxed, and in combination with the cooling conditions after hot rolling described later, it is possible to stably manufacture a hot-rolled steel sheet having a desired metal structure.
[0086] (1) Slab, slab temperature when subjected to hot rolling, and holding time The slabs to be subjected to hot rolling may be slabs obtained by continuous casting or casting and blooming, etc. Furthermore, if necessary, those which have been subjected to hot working or cold working may be used.
[0087] The slab to be subjected to hot rolling is preferably held in a temperature range of 700°C to 850°C for 900 seconds or more during heating, and then further heated and held in a temperature range of 1100°C or higher for 6000 seconds or more. When held in a temperature range of 700°C to 850°C, the steel sheet temperature may be varied within this temperature range or may be constant. When held in a temperature range of 1100°C or higher, the steel sheet temperature may be varied within the temperature range of 1100°C or higher or may be constant.
[0088] In the austenite transformation at 700°C to 850°C, Mn is distributed between ferrite and austenite, and by extending the transformation time, Mn can diffuse within the ferrite region. This eliminates Mn microsegregation unevenly distributed in the slab, and significantly reduces the standard deviation of the Mn concentration. By reducing the standard deviation of the Mn concentration, the linearity between the fracture surface and the shear surface at the end surface after shear processing can be improved. In addition, the I value can be set to a desired value. In order to reduce the standard deviation of the Mn concentration and obtain a desired I value, the holding time in the temperature range of 1100° C. or higher is preferably 6000 seconds or more. In order to obtain a desired amount of martensite and tempered martensite, the temperature at which the material is held for 6000 seconds or more is preferably 1100° C. or higher.
[0089] The hot rolling is preferably performed using a reverse mill or a tandem mill as multi-pass rolling. From the viewpoint of industrial productivity, it is more preferable to perform hot rolling using a tandem mill for at least the final several stages.
[0090] (2) Reduction rate of hot rolling: Total thickness reduction of 90% or more in the temperature range of 850 to 1100°C By performing hot rolling so that the sheet thickness is reduced by 90% or more in total in the temperature range of 850 to 1100°C, mainly recrystallized austenite grains are refined, and the accumulation of strain energy in unrecrystallized austenite grains is promoted, and the recrystallization of austenite is promoted, and the atomic diffusion of Mn is promoted, so that the standard deviation of the Mn concentration can be reduced. In addition, the I value can be set to a desired value. Therefore, it is preferable to perform hot rolling so that the sheet thickness is reduced by 90% or more in total in the temperature range of 850 to 1100°C. The thickness reduction in the temperature range of 850 to 1100°C can be expressed as (t0-t1) / t0×100(%), where t0 is the entrance thickness before the first pass in rolling in this temperature range, and t1 is the exit thickness after the final pass in rolling in this temperature range.
[0091] (3) Stress after the rolling stage before the final stage of hot rolling and before the final stage of rolling: 170 kPa or more It is preferable that the stress applied to the steel sheet after the rolling one stage before the final stage of hot rolling and before the final stage of rolling is 170 kPa or more. <001> The number of grains having a crystal orientation of {110} can be reduced. <001> Since the crystal orientation is difficult to recrystallize, suppressing the formation of this crystal orientation can effectively promote recrystallization by the final reduction. As a result, the band-shaped structure of the hot-rolled steel sheet is improved, the periodicity of the metal structure is reduced, and the E value increases. If the stress applied to the steel sheet is less than 170 kPa, the E value may not be able to be a desired value. The stress applied to the steel sheet is more preferably 190 kPa or more. The stress applied to the steel sheet can be controlled by adjusting the roll rotation speed during tandem rolling, and can be calculated by dividing the load in the rolling direction measured in the rolling stand by the cross-sectional area of the sheet being passed through.
[0092] (4) Reduction rate in the final stage of hot rolling: 8% or more, hot rolling completion temperature Tf: 900°C or more, less than 960°C It is preferable that the reduction rate in the final stage of hot rolling is 8% or more, and the hot rolling completion temperature Tf is 900°C or more. By setting the reduction rate in the final stage of hot rolling to 8% or more, recrystallization due to the reduction in the final stage can be promoted. As a result, the band-shaped structure of the hot rolled steel sheet is improved, the periodicity of the metal structure is reduced, and the E value is increased. By setting the hot rolling completion temperature Tf to 900°C or more, an excessive increase in the number of ferrite nucleation sites in austenite can be suppressed. As a result, the generation of ferrite in the final structure (metal structure of the hot rolled steel sheet after production) can be suppressed, and a high-strength hot rolled steel sheet can be obtained. In addition, by setting the hot rolling completion temperature Tf to less than 960°C, the coarsening of the austenite grain size can be suppressed, the periodicity of the metal structure can be reduced, and the E value can be set to a desired value.
[0093] (5) Stress after the final stage of hot rolling and until the steel plate is cooled to 800°C: Less than 200 kPa The stress applied to the steel sheet after the final stage of hot rolling and before the steel sheet is cooled to 800°C is preferably less than 200 kPa. By setting the stress (tension) applied in the rolling direction of the steel sheet to less than 200 kPa, austenite recrystallization preferentially proceeds in the rolling direction, and an increase in the periodicity of the metal structure can be suppressed. As a result, the E value can be set to a desired value. The stress applied to the steel sheet is more preferably 180 MPa or less. The stress applied in the rolling direction of the steel sheet can be controlled by adjusting the rotation speed of the rolling stand and the winding device, and can be obtained by dividing the measured load in the rolling direction by the cross-sectional area of the sheet being passed through.
[0094] (6) From the completion of hot rolling, accelerate cooling is performed so that the average cooling rate to 600°C is 50°C / s or more. By performing accelerated cooling from the completion of hot rolling to 600°C at an average cooling rate of 50°C / s or more, ferrite transformation, bainite transformation and / or pearlite transformation inside the steel sheet can be suppressed, and the desired strength can be obtained. In addition, the I value can be set to a desired value. If air cooling or the like is performed during accelerated cooling to 600°C after the completion of hot rolling, the amount of ferrite may increase and the I value may not be able to be set to a desired value, which is not preferable. Although the upper limit of the average cooling rate is not particularly specified, a faster cooling rate requires larger cooling equipment and higher equipment costs. Therefore, in consideration of equipment costs, the average cooling rate of the accelerated cooling is preferably 300° C. / s or less.
[0095] The average cooling rate referred to here means the temperature drop of the steel plate from the start of accelerated cooling (the time when the steel plate is introduced into the cooling equipment) to 600°C divided by the time required from the start of accelerated cooling until the temperature of the steel plate reaches 600°C.
[0096] In the cooling after the completion of hot rolling, it is more preferable to cool to a temperature range of the hot rolling completion temperature Tf-50 ° C. within 1 second after the completion of hot rolling. That is, it is more preferable to set the cooling amount for 1 second after the completion of hot rolling to 50 ° C. or more. This is because the growth of austenite grains refined by hot rolling can be suppressed. In order to cool to a temperature range of the hot rolling completion temperature Tf-50 ° C. or less within 1.0 second after the completion of hot rolling, cooling with a large average cooling rate may be performed immediately after the completion of hot rolling, for example, by spraying cooling water on the steel sheet surface. By cooling to a temperature range of Tf-50 ° C. or less within 1 second after the completion of hot rolling, the crystal grain size of the surface layer can be refined, and the bending internal crack resistance of the hot rolled steel sheet can be improved. After cooling to the temperature range of the hot rolling completion temperature Tf-50°C within 1 second after the completion of hot rolling, accelerated cooling may be performed to 600°C at an average cooling rate of 50°C / s or more, as described above.
[0097] (7) Cool so that the average cooling rate in the temperature range of 450 to 600°C is 30°C / s or more and less than 50°C / s. After the accelerated cooling is completed, it is preferable to cool the material so that the average cooling rate in the temperature range of 450 to 600°C is 30°C / s or more and less than 50°C / s. By setting the average cooling rate in the temperature range to 30°C / s or more and less than 50°C / s, the CS value can be set to a desired value. If the average cooling rate exceeds 50°C / s, coarse crystal grains are likely to be generated in the metal structure, and the CS value is -8.0×10 5 When the average cooling rate is less than 30°C / s, the strength of the hard structure increases and the strength difference with the soft structure increases, so the CS value is less than 8.0×10 5 Become super. The average cooling rate referred to here means the temperature drop of the steel plate from the cooling stop temperature of accelerated cooling with an average cooling rate of 50°C / s or more to the cooling stop temperature of cooling with an average cooling rate of 30°C / s or more and less than 50°C / s, divided by the time required from the stop time of accelerated cooling with an average cooling rate of 50°C / s or more to the stop time of cooling with an average cooling rate of 30°C / s or more and less than 50°C / s.
[0098] (8) Average cooling rate in the temperature range from coiling temperature to 450°C: 50°C / s or more In order to suppress the area ratio of pearlite and obtain the desired strength, it is preferable to set the average cooling rate in the temperature range from the coiling temperature to 450° C. to 50° C. / s or more, which makes it possible to harden the matrix structure. The average cooling rate referred to here means a value obtained by dividing the temperature drop of the steel sheet from the cooling stop temperature to the coiling temperature in the case where the average cooling rate is 30°C / s or more and less than 50°C / s, by the time required from the stop of cooling to coiling in the case where the average cooling rate is 30°C / s or more and less than 50°C / s.
[0099] (9) Winding temperature: 350°C or less The coiling temperature is preferably 350°C or less. By setting the coiling temperature to 350°C or less, the driving force for transformation from austenite to bcc can be increased, and the deformation strength of austenite can be increased. Therefore, when transforming from austenite to martensite, the hard phase is uniformly distributed, and the variation can be improved. As a result, the I value can be reduced, and the linearity of the boundary between the fracture surface and the shear surface at the end surface after shear processing can be improved. Therefore, the coiling temperature is preferably 350°C or less. EXAMPLES
[0100] Next, the effect of one embodiment of the present invention will be described in more detail with reference to an example, but the conditions in the example are merely an example of conditions adopted to confirm the feasibility and effect of the present invention, and the present invention is not limited to this example of conditions. Various conditions may be adopted in the present invention as long as they do not deviate from the gist of the present invention and the object of the present invention is achieved.
[0101] Steels having the chemical compositions shown in Tables 1 and 2 were melted and continuously cast into slabs with thicknesses of 240 to 300 mm. The resulting slabs were used to obtain hot-rolled steel sheets shown in Tables 5 and 6 under the manufacturing conditions shown in Tables 3 and 4. In addition, Production No. 11 was cooled to 791° C. after completion of hot rolling, and then air-cooled for 5.0 seconds. The average cooling rate during air-cooling was less than 5.0° C. / s.
[0102] The area ratio of the metal structure, E value, I value, CS value, standard deviation of Mn concentration, average crystal grain size of the surface layer, tensile strength (TS), and hole expansion ratio (λ) were measured for the hot-rolled steel sheets obtained by the above-mentioned methods. The measurement results are shown in Tables 5 and 6. The remaining structure was one or two of bainite and pearlite.
[0103] Evaluation method for the properties of hot-rolled steel sheets Tensile strength When the tensile strength (TS) was 980 MPa or more, it was judged to have high strength and to pass, whereas when the tensile strength (TS) was less than 980 MPa, it was judged to not have high strength and to fail.
[0104] Hole expansion ratio When the hole expanding ratio (λ) was 55% or more, the specimen was judged to have excellent hole expandability and to pass the test. On the other hand, when the hole expanding ratio was less than 55%, the specimen was judged to have poor hole expandability and to fail the test.
[0105] Limiting thickness reduction rate at break The critical thickness reduction rate at break of the hot-rolled steel sheets was evaluated by a tensile test. The tensile test was carried out in the same manner as when the tensile properties were evaluated. The thickness before the tensile test was t1, and the minimum thickness at the center of the width direction of the tensile test piece after fracture was t2. The limiting fracture thickness reduction rate was obtained by calculating the value of (t1-t2) x 100 / t1. The tensile test was carried out five times, and the limiting fracture thickness reduction rate was obtained by calculating the average value of the three times excluding the maximum and minimum values of the limiting fracture thickness reduction rate.
[0106] When the critical fracture thickness reduction rate was 75.0% or more, the hot-rolled steel sheet was judged to have a high critical fracture thickness reduction rate and to have passed the test. On the other hand, when the critical fracture thickness reduction rate was less than 75.0%, the hot-rolled steel sheet was judged to have a high critical fracture thickness reduction rate and to have failed the test.
[0107] Shear workability (evaluation of the linearity of the boundary between the fracture surface and the shear surface) Among the shear workability of the hot-rolled steel sheets, the linearity of the boundary between the fracture surface and the shear surface was evaluated by conducting a punch-out test and determining the linearity of the boundary between the fracture surface and the shear surface. Five punched holes were created at the center of the width of a hot-rolled steel sheet with a hole diameter of 10 mm, a clearance of 15%, and a punching speed of 3 m / s. Next, the appearance of 10 end faces parallel to the rolling direction (two end faces per punched hole) of the five punched holes was photographed using an optical microscope. In the obtained observation photograph, the end face shown in Figure 1(a) can be observed. As shown in Figures 1(a) and 1(b), sagging, shear surfaces, fracture surfaces, and burrs are observed on the end faces after punching. Note that Figure 1(a) is a schematic diagram of the end face parallel to the rolling direction of the punched hole, and Figure 1(b) is a schematic diagram of the side of the punched hole. Sagging is a smooth R-shaped surface, a shear surface is a punched end face separated by shear deformation, a fracture surface is a punched end face separated by a crack generated near the cutting edge after the end of shear deformation, and a burr is a surface with a protrusion protruding from the lower surface of the hot-rolled steel sheet.
[0108] In the observation photographs of 10 end faces obtained from the five end faces, the straightness at the boundary between the fracture surface and the shear was measured by the method described below, and the maximum straightness obtained was calculated.
[0109] The linearity at the boundary between the fracture surface and the shear surface was obtained by the following method. As shown in Figure 1(b), the boundary points between the shear plane and the fracture plane (points A and B in Figure 1(b)) were determined for the end face. The length of the distance x connecting points A and B with a straight line was measured. Next, the length y of the curve along the boundary between the fracture plane and the shear plane was measured. The value obtained by dividing the obtained y by x was taken as the straightness at the boundary between the fracture plane and the shear plane.
[0110] When the maximum straightness value obtained in the punching test was less than 1.045, the hot-rolled steel sheet was judged to have excellent shear workability and to have passed the test. On the other hand, when the maximum straightness value obtained was 1.045 or more, the hot-rolled steel sheet was judged to be unacceptable since it did not have excellent shear workability.
[0111] Resistance to internal cracking when bent The bending test pieces were cut out from the hot-rolled steel plate at half the width direction of the plate to have a rectangular shape of 100 mm x 30 mm, and the resistance to internal bending cracking was evaluated by the following bending test. Tests were conducted in accordance with the V-block method (bending angle θ is 90°) of JIS Z 2248:2006 for both bending in which the bending ridgeline is parallel to the rolling direction (L direction) (L-axis bending) and bending in which the bending ridgeline is parallel to the direction perpendicular to the rolling direction (C direction) (C-axis bending). From this, the minimum bending radius at which cracks do not occur was determined, and resistance to internal bending cracking was investigated. The average value of the minimum bending radii in the L axis and C axis divided by the plate thickness was taken as the limit bending R / t, which was used as an index value for resistance to internal bending cracking. If R / t was 3.0 or less, it was determined that the hot-rolled steel plate had excellent resistance to internal bending cracking.
[0112] However, to determine the presence or absence of cracks, the cross section of the test piece after the test was cut parallel to the bending direction and perpendicular to the plate surface, mirror-polished, and then observed for cracks under an optical microscope. If the length of the crack observed on the inside of the bent test piece exceeded 30 μm, it was determined that a crack was present.
[0113] [Table 1]
[0114] [Table 2]
[0115] [Table 3]
[0116] [Table 4]
[0117] [Table 5]
[0118] [Table 6]
[0119] From Tables 5 and 6, it can be seen that the hot-rolled steel sheets according to the examples of the present invention have high strength and critical thickness reduction rate at break, as well as excellent hole expandability and shear workability. In addition, it can be seen that the hot-rolled steel sheets according to the examples of the present invention, which have an average crystal grain size of the surface layer of less than 3.0 μm, have excellent internal crack resistance in addition to the above-mentioned properties. On the other hand, it is found that the hot-rolled steel sheets according to the comparative examples are deteriorated in at least one of the strength, the critical sheet thickness reduction rate at break, the hole expandability, and the shear workability. [Industrial Applicability]
[0120] According to the above-mentioned aspect of the present invention, it is possible to provide a hot-rolled steel sheet having high strength and a critical thickness reduction rate at break, as well as excellent hole expandability and shear workability. In addition, according to the above-mentioned preferred aspect of the present invention, it is possible to obtain a hot-rolled steel sheet having the above-mentioned properties and further suppressing the occurrence of internal cracks in bending, i.e., having excellent resistance to internal cracks in bending. The hot-rolled steel sheet according to the present invention is suitable as an industrial material used for automobile parts, machine structural parts, and further building parts.
Claims
1. The chemical composition, in mass%, is C: 0.040-0.250%, Si: 0.05-3.00%, Mn: 1.00-4.00%, sol. Al: 0.001 to 0.500%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, Ti: 0-0.300%, Nb: 0 to 0.100%, V: 0 to 0.500%, Cu: 0-2.00%, Cr: 0-2.00%, Mo: 0-1.00%, Ni: 0-2.00%, B: 0 to 0.0100%, Ca: 0-0.0200%, Mg: 0 to 0.0200%, REM: 0-0.1000%, Bi: 0 to 0.0200%, As: 0 to 0.100%, Zr: 0 to 1.00%, Co: 0-1.00%, Zn: 0 to 1.00%, W: 0-1.00%, Sn: 0 to 0.05%, and The balance is Fe and impurities. The following formula (A) is satisfied: The metal structure is, in area percent, The total content of martensite and tempered martensite is more than 92.0% and is not more than 100.0%; The retained austenite is less than 3.0%; Ferrite is less than 5.0%; The entropy value, which is obtained by analyzing an SEM image of the metal structure by a gray level co-occurrence matrix method and is represented by the following formula (1), is 11.0 or more, The inverse differencing normalized value represented by the following formula (2) is less than 1.020, The Cluster Shade value represented by the following formula (3) is −8.0×10 5 ~8.0 x 10 5 and The standard deviation of the Mn concentration is 0.60 mass% or less; A hot-rolled steel sheet having a tensile strength of 980 MPa or more. Zr+Co+Zn+W≦1.00%…(A) However, each element symbol in the formula (A) indicates the content of the element in mass %, and 0% is substituted when the element is not contained. Here, P(i,j) in the following formulas (1) to (5) is a gray level co-occurrence matrix, L in the following formula (2) is the number of possible gray scale levels of the SEM image, i and j in the following formulas (2) and (3) are natural numbers from 1 to L, and μ in the following formula (3) is x and μ y are represented by the following formulas (4) and (5), respectively. [0010] [0025] [0030] [0045] [0050]
2. The hot-rolled steel sheet according to claim 1, characterized in that the average crystal grain size of the surface layer is less than 3.0 µm.
3. The chemical composition, in mass%, Ti: 0.001-0.300%, Nb: 0.001 to 0.100%, V: 0.001-0.500%, Cu: 0.01-2.00%, Cr: 0.01-2.00%, Mo: 0.01-1.00%, Ni: 0.01-2.00%, B: 0.0001 to 0.0100%, Ca: 0.0001-0.0200%, Mg: 0.0001-0.0200%, REM: 0.0001-0.1000%, Bi: 0.0001-0.0200%, As: 0.001 to 0.100%, Zr: 0.01 to 1.00%, Co: 0.01 to 1.00%, Zn: 0.01-1.00%, W: 0.01 to 1.00%, and Sn: 0.01~0.05% The hot-rolled steel sheet according to claim 1 or 2, further comprising one or more selected from the group consisting of:
Citation Information
Patent Citations
Hot rolled steel sheet
JP2015098629A
Hot rolled steel sheet and production method therefor
JP2015214718A
700mpa high strength hot rolling q&p steel and manufacturing method thereof
WO2014166323A1
Hot-rolled steel sheet and production method therefor, cold-rolled steel sheet and production method therefor, production method for cold-rolled annealed steel sheet, and production method for hot-dip galvanized steel sheet
WO2020044445A1
Hot-rolled steel sheet
WO2020184372A1